Regenerative periapical surgery: A case report - Sonam Bhandari; T S Ashwini; Reshma Naik; Tushar Bandiwadekar; Saleem Makandar (Wolters Kluwer Medknow Publications, 2013)
Introduction: Periapical surgery is an important treatment alternative in the presence of a large periapical cyst. To achieve optimal healing and regeneration of the bone different bone substitutes can be used. Case Report: A 35 year old male patient reported with the soft diffuse swelling in anterior palatal region and drainings in us with 21 labially. He had a history of trauma 5 years back. The clinical and radiographic diagnosis of infected periapical cyst with 11,21; invasive cervical root resorption with 21 and internal root resorption with 11 was made. Endodontic treatment was performed with11,2 followed by periapical curettage. A picectomy and retrograde filling with white mineral trioxide aggregate (MTA) was carried out with 11,21. The cervical resorption defect with 21 was restored with white MTA. Platelet rich fibrin (PRF) was mixed with demineralised bone matrix (Osseograft) and used as a regenerative biomaterial in the periapiacl defect. 14 months follow up shows satisfactory healing and regeneration of periapical region. Discussion: There is considerable clinical interest in using PRF alone or in combination with graft materials as it is a reservoir of many growth factors and have potential for accelerated soft-and hard tissue healing. PRF is a new generation of platelet concentrate, derived from patients own blood.